Evaluation of dynamic mechanical properties of fique fabric/epoxy composites (2019)
The fique is a plant typical of the Colombian Andes, from which relatively common items are fabricated. One of these is woven fabric extensively applied in sackcloths. The mechanical strength of fique fabric have motivated recent investigations on possible reinforcement of polymer matrix composites. For this purpose its thermo-mechanical behavior was unveiled. In particular, dynamic mechanical analysis (DMA) of fique fabric reinforced polyester matrix composites disclosed improved viscoelastic behavior in association with change in the glass transition temperature. The present work extends this investigation to epoxy matrix, which is one of the most employed thermoset polymer for composite matrix. Fique fabric volumetric fractions of up to 50% are for the first time incorporated into epoxy composites. It was found that these incorporations significantly increased the viscoelastic stiffness of the composite, given by the storage modulus (E’), in the temperature interval from -50 to 170°C. An accentuated softening in viscoelastic stiffness was revealed for all composites above 75°C. Peaks in both the loss modulus (E”) and tangent delta (tan δ), respectively associated with the lower and upper limits of the glass transition temperature, were shifted towards higher temperatures with increasing amount of fique fabric.